ChemInform Abstract: 6‐Triazolyl‐Substituted Sulfocoumarins Are Potent, Selective Inhibitors of the Tumor‐Associated Carbonic Anhydrases IX and XII. Issue 31 (5th August 2014) - Grandane, Aiga; Tanc, Muhammet; Zalubovskis, Raivis; Supuran, Claudiu T.
Abstract A variety of 6‐substituted sulfocoumarins incorporating triazolyl moieties are synthesized by employing click chemistry.